Cyclospora cayetanensis: First report of imported and autochthonous infections in Kuwait - Jamshaid Iqbal; Parsotam Ravjee Hira; Faiza Al-Ali; Nabila Khalid (Journal of Infection in Developing Countries)
Introduction: The intestinal coccidian parasites Cryptosporidium spp. and Cyclospora cayetanensis have emerged as significant human pathogens worldwide. The reports of Cyclospora cayetanensis infection in the Middle East are sporadic and no case has been reported from Kuwait.